Paradoxes in Borderline Emotional Dysregulation in Adolescence: Influence of Parenting, Stressful Life Events, and Attachment - Robin, Marion; Belbèze, Jean; Pham-Scottez, Alexandra; Shadili, Gérard; Peres, Victoire; Silva, Jérôme; Corcos, Maurice; Speranza, Mario (Frontiers in Psychiatry, 2021)
Introduction: Borderline personality disorder (BPD) in adolescents is characterized by emotional dysregulation, insecure attachment, an history of stressful life events (SLE) as well as dysfunctional parent-child interactions. The respective contribution of each of these factors on BPD affective symptoms is not yet clear. The purpose of this study is to assess the distinct impact of parental adversity and SLE on BPD affective symptoms and the role of attachment and alexithymia in such emotional processes. Method: This study explored parental dysfunction and SLE as predictors of affective symptoms of BPD and of attachment insecurity, in BPD adolescents (n = 85) and healthy controls (n = 84) aged 13 to 19 from the European Research Network on BPD (EURNET-BPD). The links between adversity and BPD symptoms were also investigated by emotional dysregulation assessment, as measured by alexithymia and hopelessness. Results: Dysfunctional parental interactions were linked to affective symptoms, hopelessness and anxious attachment, in healthy controls but not in BPD. Cumulative SLE were positively correlated to affective symptoms and avoidant attachment in the control group, but negatively correlated to both these variables in BPD. Multivariate regression analysis revealed that, in BPD, affective symptoms were independent of dysfunctional parenting but depended on attachment, whereas in controls, a maternal affectionless control style directly predicted affective symptoms. Moreover, increasing numbers of SLE reduced affective symptoms in BPD, independently of parental interactions or attachment, and were associated with growing use of operative thinking. Discussion: BPD patients showed paradoxical emotional reactions: there was no increase of hopelessness and affective symptoms with an increased parental dysfunction, but a decrease in affective symptoms and hopelessness with cumulative SLE. Two pathways arose, one involving attachment as an emotional dysregulation process for parent-child interactions, and a second one for SLE, with a more direct pathway to affective symptoms, independent of attachment, but dependent on early interactions, and involving alexithymia. In sum, adversity factors have distinct effects in BPD and attachment is partly accountable for affective symptoms independently of adversity. Our results suggest that in highly insecure conditions, cumulative adversity may produce paradoxical effects, including a lesser expression of affective symptoms and hopelessness.